Preprocedural fasting for coronary interventions: is it time to change practice? - Wijeyeratne, Yanushi Dullewe; Wendler, Renate; Spray, Dominic; Bunce, Nick (Heart (British Cardiac Society), 2014)
[...]practice is largely based on often poorly referenced local guidelines that differ between institutions.